Free Virtual Navigation Using Motor Imagery Through an Asynchronous Brain–Computer Interface - Velasco-Álvarez, Francisco Javier; Ron-Angevin, Ricardo; Blanca-Mena, María José (MIT Press, 2010)
In this paper, an asynchronous brain-computer interface is presented that enables the control of a wheelchair in virtual environments using only one motor imagery task. The control is achieved through a graphical intentional control interface with three navigation commands (move forward, turn right, and turn left) which are displayed surrounding a circle. A bar is rotating in the center of the circle, so it points successively to the three possible commands. The user can, by motor imagery, ex- tend this bar length to select the command at which the bar is pointing. Once a command is selected, the virtual wheelchair moves in a continuous way, so the user controls the length of the advance or the amplitude of the turns. Users can volun- tarily switch from this interface to a noncontrol interface (and vice versa) when they do not want to generate any command. After performing a cue-based feed- back training, three subjects carried out an experiment in which they had to navi- gate through the same fixed path to reach an objective. The results obtained sup- port the viability of the system.
Keywords: Realidad virtual - Navegación; Electroencephalographic (EEG) signals; Mental tasks; Motor imagery